2013
DOI: 10.1002/bio.2496
|View full text |Cite
|
Sign up to set email alerts
|

Changes in immune functions during a peaking period in male university soccer players

Abstract: The concept of peaking ensures that athletes have trained to attain their absolute peak performance levels prior to a competition. This study investigates the effects of peaking on the functions of neutrophils and lymphocytes in university soccer players during a five-day soccer training camp followed by two weeks of tapering. The study subjects were 22 soccer players who were members of a university soccer club. We carried out our investigation during a five-day training camp and two weeks after the training … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 43 publications
1
4
0
1
Order By: Relevance
“…Ueno et al [ 16 ] suggested that a 2-week tapering period seems to be enough time for muscle adaptation and recovery to occur after athletes attended an intensive training camp, which is consistent with the results of our research. At T3 (after training at home), we saw changes that probably reflect the “repeated bout effect”, such that skeletal muscle tissue adapts after the first session of damaging exercise.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Ueno et al [ 16 ] suggested that a 2-week tapering period seems to be enough time for muscle adaptation and recovery to occur after athletes attended an intensive training camp, which is consistent with the results of our research. At T3 (after training at home), we saw changes that probably reflect the “repeated bout effect”, such that skeletal muscle tissue adapts after the first session of damaging exercise.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, only the neutrophil counts tended to decrease after 5 days of intensive training loads, which suggested that neutrophil cells were most affected by intensive exercise among white blood cells. In contrast, Ueno et al [ 16 ] did not observe any change in neutrophil counts before and after 5 days of an intensified training camp, and two weeks after the training camp. On the other hand, in healthy untrained adults, neutrophil counts fell below pre-exercise values after 2 and 3 days of acute exercise bout, before gradually returning to basal levels [ 19 ].…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Especula-se que um maior período de polimento poderia proporcionar uma maior redução neste marcador de dano muscular. Especialmente, considerando que apesar de evidências mostrarem bons resultados com uma semana de polimento 23,24 , existe um volume maior de estudos atestando duas semanas como o ideal [25][26][27] . A CK é o marcador que tem sido melhor associado com o desgaste tecidual muscular 28 .…”
Section: Discussionunclassified